A Standard Preparation of Bovine Fibrinogen - Landaburu, Ricardo H.; Curtino, Juan (Thrombosis and Haemostasis, 1964)
The correlation of values given by different research laboratories that work on blood coagulation is difficult on account of the difference of reagents used. Fibrinogen is the most important source of variations in results when research is done using purified substances. A reproducible procedure that gives a stable and sensitive bovine fibrinogen is given. The material obtained has been studied on its properties.